2014
DOI: 10.4149/av_2014_01_43
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein analysis of chicken skin infected with Marek΄s disease virus

et al.

Abstract: Summary. -The skin and feather follicle epithelia of birds infected with Marek's disease virus (MDV) are the sites of infectious virus particle formation and shedding. However, the host responses and protein networks involved in the production of virus particles in the skin of MDV-infected chickens are poorly understood. This current study aimed to analyze the differential protein expression patterns in skin between MDV-infected and uninfected specific pathogen-free (SPF) chickens 28 days post infection (dpi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The present study revealed that VIM have potential function of regulating coat color formation. Studies have proven that TTR protein expression was decreased in Marek's disease-infected chickens, with iris discoloration and dark coat color [24]. However, which pigment synthesis factor and TTR affect to regulate the formation of hair color, it is not clear at present.…”
Section: Discussionmentioning
confidence: 96%
“…The present study revealed that VIM have potential function of regulating coat color formation. Studies have proven that TTR protein expression was decreased in Marek's disease-infected chickens, with iris discoloration and dark coat color [24]. However, which pigment synthesis factor and TTR affect to regulate the formation of hair color, it is not clear at present.…”
Section: Discussionmentioning
confidence: 96%
“…Proteomics methodologies have been applied extensively in the study of Marek disease (Haq et al 2010, Kunec 2013. Changes in relevant proteomes have been reported by Thanthrige-Don et al (2009, 2010 in the spleen, Lu et al (2010) in the Fabricius bursa, Hu et al (2012) in the thymus samples, in the liver and Chen, Hu et al (2014) in cutaneous skin tissues after infection with Marek Disease Virus. Further, Kumar et al (2012) have investigated molecular mechanisms of neoplastic transformation in Marek disease, as a model for studying human lymphomas, and found that NF-kappa B is a key protein complex in neoplastic transformation of CD30-expressing lymphocytes in vivo during the disease.…”
Section: Studies In Chickensmentioning
confidence: 99%